Effects of zingiberaceae based botanical pesticides biopesticides and deltamethrin insecticide to the activities of cocoa black ants, Dolichoderus thoracicus (Smith) - Saripah Bakar,; Siti Noor Hajjar Md Latip,; Zhang, Aijun; Alias Awang, (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2021)
Cocoa pod borer, Conopomorpha cramerella is is the most devastating pest responsible for the decline of cocoa production in Southeast Asia. Several control methods have been implemented to reduce the impact of C. cramerella including application of the botanical pesticides. Hence, very few reports on the botanical pesticide and insecticide effect on the beneficial insect associated with cocoa ecosystems had been reported in Malaysia. This study investigates the effect of botanical pesticide and insecticide on the cocoa black ants (CBA), Dolichoderus thoracicus, a biological control agent against the C. cramerella. Four Zingiberaceae based botanical pesticides formulations were applied: Alpinia galanga F1, A. galanga F2, Zingiber officinale F1, Z. officinale F2 with insecticide (a.i deltamethrin), and water as control treatment. The introduction of artificial ant nests stuffed with dry cocoa leaves was carried out with two different fields observation with six replicates. The acoustic strength in decibel (dB) of D. thoracicus population was observed for 60-days at three intervals; natural sound, 5-seconds, and 30-seconds after minor disturbance of the nests. Results denoted that D. thoracicus actively moves into the nests started to increase from day-10. The highest activity was observed in day-60 (60.139 a) and significantly different (p < 0.05) from the first 30 days of observation. Zingiber officinale and A. galanga formulations performed better than deltamethrin, regarding the D. thoracicus activities. The decibel derived from ecoacoustic sound showed almost similar results between treatments and suggested the stability of D. thoracicus population between treated and non-treated nests. The results suggest the artificial ant nests constructed with treated dry cocoa leaves either with Zingiberaceae formulations or insecticide may have less effect to the activity of D. thoracicus. The Zingiberaceae based botanical pesticide is safe for beneficial insects of cocoa at a lower dose, and can be applied for D. thoracicus population built-up strategies in the future.